Analisis Spasial Beban Limbah Budidaya Tambak Terhadap Lingkungan Perairan Pesisir Holtekamp Kota Jayapura, Provinsi Papua - Barnabas Bara'padang; Achmad Fahrudin; Irzal Effendi (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
This study was conducted to determine water quality conditions and the carrying capacity of Holtekamp coastal, to identify the aquaculture activities that contribute waste on coastal and impact of aquaculture waste load. Water and plankton samples were collected from fish ponds (tambak), Kali Buaya channel and sea. Questionnaires were administered to 25 farmers. Results of water quality analyses showed that Holtekamp coastal water is characterized with higher concentration of BOD5 (Biological oxygen demand), N-total, COD (chemical oxygen demand) and TOM (total organic matter) 4.96 mg/l, 4.19 mg/l, 33.53 mg/l, and 22.18 mg/l, turbidity (7.02 NTU) and TSS (total suspended solids) 201.67 mg/l were higher in Kali Buaya chanal and PO4-P (2.08) in fishpond. The carrying capacity of coastal water is 10.452.915 m3 and a maximum of effluents 104.529 m3, respectively.Key Words: Ponds; Effluents; Water quality; Carrying capacity; Holtekamp